PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI, PENGEMBANGAN KARIER DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Edi Santoso, 09.05.51.0020 (Students Journal of Economic and Management, 2013)
This research aim to examined the effect of transformational leadership, motivation, career development and work discipline on employee performance. In this study, researchers used a sample of 102 respondents employees of PT. Luxindo Nusantara Semarang, the data obtained from the questionnaire. Questionnaire data were then tested with the validity and reliability, having obtained a valid result, then studies using multiple linear regression to describe the relationship between these variables. The result is a hypothesis that transformational leadership, motivation and working discipline of positive on employee performance, but career development does not significantly on the performance of employees.Keywords: Transformational Leadership, Motivation, Career Development, Work Discipline and Employee Performance.